SEARCH PATH IN ROUTE NETWORK OF BRANCHES CONTAINS METHODS AND LIMITS - , О. Ф. (Municipal economy of cities (Technical science), 2013)
The algorithm for solution of the problem finding the shortest paths over time in urban traffic network transport